KONSERVASI SUMBER DAYA ALAM HAYATI BERBASIS ETNOBIOPEDAGOGI (KAJIAN TEORITIS) - N. Putri Sumaryani; I Nengah Suka Widana; Putu Ryan Widyastaguna; Ni Nyoman Parmithi (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
The research objectives are to (1) define the basic concepts of ethnobiopedagogy, (2) determine the relevance of local wisdom in preserving biodiversity, (3) determine strategies and forms of integration of ethnobiopedagogy in education and conservation. (4) to find out the challenges and opportunities in its implementation. To achieve this goal, a theoretical literature review was carried out using sources relevant to material on the conservation of biological natural resources based on ethnobiopedagogy (ethnobiology, pedagogy). Conclusions from the theoretical study include: (a) Ethnobiopedagogy is a strategy, an innovative approach in the conservation of biological resources that focuses on the field of education by integrating ethnic values, pedagogy and biology. (b) Local wisdom in preserving biodiversity has very strong and deep relevance. (c) Integration of Ethnobiopedagogy in Education and Conservation, as an intersection of at least three components, namely formal and non-formal education; forms of local wisdom traditions that still exist; and use of Information and Communication Technology. (d) Challenges in implementing Ethnobiopedagogy, namely low human resources, lack of curriculum integration, and the threat of modernization to local wisdom practices.